2023
DOI: 10.1200/edbk_390738
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Germline Cancer Predisposition With Tumor-Based Next-Generation Sequencing for Modern Oncology Diagnosis, Interception, and Therapeutic Development

Abstract: In the era of precision medicine, genomic interrogation for identification of both germline and somatic genetic alterations has become increasingly important. While such germline testing was usually undertaken via a phenotype-driven single-gene approach, with the advent of next-generation sequencing (NGS) technologies, the widespread utilization of multigene panels, often agnostic of cancer phenotype, has become a commonplace in many different cancer types. At the same time, somatic tumor testing in oncology p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…While the CHEK1 gene is included in some commercial NGS panels designed for assessing hereditary cancer risk ( 49 ), the available data regarding germline CHEK1 mutations and cancer risk are limited. In a study involving 48 women with inherited ovarian cancer lacking BRCA1 or BRCA2 mutations, a CHEK1 exon 7 c.1564-1565insA frameshift mutation was identified ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the CHEK1 gene is included in some commercial NGS panels designed for assessing hereditary cancer risk ( 49 ), the available data regarding germline CHEK1 mutations and cancer risk are limited. In a study involving 48 women with inherited ovarian cancer lacking BRCA1 or BRCA2 mutations, a CHEK1 exon 7 c.1564-1565insA frameshift mutation was identified ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the era of precision medicine, the integration of germline and somatic genetic profiling is gaining a central role in medical oncology. Indeed, germline and somatic genetic testing may help personalize therapeutic decisions for targeted therapies according to each patient’s mutational status [ 230 ]. Moreover, germline characterization of genetic variants underlying cancer susceptibility may enable the identification of individuals at risk of developing a particular cancer and guide precision prevention strategies [ 231 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the expected growth in eligibility for hereditary cancer services, it is also worth considering the implications of a potential acceleration in the move towards integrating hereditary cancer genetics into oncology clinics. On the one hand, commercial next generation sequencing (NGS)-based tumour testing panels often include numerous genes linked to hereditary cancer [ 22 ] and recent studies have found that 4.3%–16% of patients undergoing tumour testing have been found to carry pathogenic (P) or likely pathogenic (LP) germline variants [ 23 ]. Given this overlap and the growing relevance of germline variants to treatment selection, greater integration of tumour and germline testing may be advisable [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, commercial next generation sequencing (NGS)-based tumour testing panels often include numerous genes linked to hereditary cancer [ 22 ] and recent studies have found that 4.3%–16% of patients undergoing tumour testing have been found to carry pathogenic (P) or likely pathogenic (LP) germline variants [ 23 ]. Given this overlap and the growing relevance of germline variants to treatment selection, greater integration of tumour and germline testing may be advisable [ 23 ]. Our workforce requirements model takes this dynamic into account through Pathway 6 ( Figure 1 ), which in the base case assumes that 11.5% of new cancer patients receive tumour testing and P/LP germline mutations are detected in 3% of those patients, which leads to Pathway 6 only accounting for about 1% of the caseload and <1% of FTE requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation